2019
DOI: 10.7454/msk.v23i2.10632
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression of selected apoptotic markers in human oral squamous carcinoma HSC-3 cell line treated with Myrmecodia pendans plant extract

Abstract: Background: Myrmecodia pendans (M. pendans), or Sarang Semut, is an epiphyte with anticancer potential. It was recently reported that it induces apoptotic activity in the human oral squamous carcinoma (HSC-3) cell line. This study aimed to investigate the effect of M. pendans treated samples on the expression of apoptotic markers, Bax and Bcl-2. Methods: M. pendans was purchased from West Papua, Indonesia. The hypocotyl was dried thoroughly and then extracted aqueously. The apoptotic activity was detected via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Apoptosis, or cell death, is a closely controlled process that is initiated by either of the following two pathways: the death receptor (extrinsic) or the mitochondrial (intrinsic) pathway. 28 The anti-cancer activity widely reported in this systematic review is by inhibiting cell proliferation through intrinsic pathways.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Apoptosis, or cell death, is a closely controlled process that is initiated by either of the following two pathways: the death receptor (extrinsic) or the mitochondrial (intrinsic) pathway. 28 The anti-cancer activity widely reported in this systematic review is by inhibiting cell proliferation through intrinsic pathways.…”
Section: Discussionmentioning
confidence: 95%
“…The bioactive compounds of kaempferol and quercetin induce increased caspase-8 and −9 activity The kaempferol and quarcetin compounds of acetylacetic extract Rasamala leaf can inhibit the proliferation of human SP-C1 tongue cancer cells in vitro 21. Lestari W, et al 28 2019 S1 Myrmecodia pendans (sarang semut) Note: Aqua extract Bintuni (West Papua) HSC-3 cell Oral Squamous Cell Carcinoma Flow cytometric analysis and qRT-PCR Inhibits cell proliferation of SP-C1 cancer cell The IC50 value of kaempferol from Rasamala leaf extract is 2.50 μM; while the IC50 quarcetin value of Rasamala leaf extract is 2.31 μM Quarcetin has a higher cytotoxic effect than kaempferol in Rasamala leaf extract, but both have a high cytotoxic effect 22. Wihadmadyatami H, et al 29 2019 Q1 Ocimum sanctum Linn.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many assays have been used to evaluate the toxicity activities of Myrmecodia species that associated with the potential of anticancer activity. Some crude extracts and compounds showed the inhibitory activity against various in vitro cancer cell lines (Table 2) [48], [49], [50], [51], [52], [53], [54], [55], [56], [57], [58]. Besides, Suharyanto and Purwono reported that M. pendens had effective anticancer activity in vivo model series.…”
Section: Cytotoxic Activitymentioning
confidence: 99%